Development and validation of structural models of human posture - Barauskas, R.; Krušinskiene, R. (Mathematical Modelling and Analysis, 2006)
A time law of small vibrations of the center of pressure (COP) of humans in standing position (human posture) provides a useful information about the physical and health condition of an individual. In this work controlled inverted pendulum (CIP) model with a single degree of freedom (DOF) is used in order to simulate the vibration of COP of a human body in anterio‐posteriori (forward‐backward) direction during still standing. A method for identification of the CIP model parameters is based on numerical computation of the sensitivities of the penalty‐type error function to small variations of model parameters. The approach is applicable to structural models with any number of DOF and any structural complexity. Numerical example demonstrates the model parameter identification results providing nearly the best match of the model behaviour to the real experimental record of COP position.First Published Online: 14 Oct 2010